PENGUATAN EDUKASI ANTI-BULLYING DALAM KONTEKS PERMASALAHAN ANAK BERKEBUTUHAN KHUSUS (ABK) DI SDN PANDANTOYO 02 - Aziz Miftahus Surur; Muhammad Da’i Bachtiar; Ratna Dwiyanti; Intania Wahyuningrum (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This community service program aims to enhance both students’ and teachers’ awareness of the importance of anti-bullying education in fostering a safe and inclusive learning environment. The program employed a participatory approach based on Asset-Based Community Development (ABCD) through socialization, teacher training, and interactive student activities that identified and utilized the existing potentials, assets, and strengths within the school and its surrounding community. The results indicate a notable improvement in students’ awareness of diversity and respect for differences, an increase in teachers’ competence in addressing bullying cases, and the formation of a more inclusive and supportive school climate for CSN. This program is expected to contribute to the sustainable strengthening of inclusive education practices within elementary schools.